ASIC1a stimulates the resistance of human hepatocellular carcinoma by promoting EMT via the AKT/GSK3β/Snail pathway driven by TGFβ/Smad signals. Issue 10 (14th April 2022) - Zhang, Yinci; Cao, Niandie; Gao, Jiafeng; Liang, Jiaojiao; Liang, Yong; Xie, Yinghai; Zhou, Shuping; Tang, Xiaolong
Abstract: Multidrug resistance is the main obstacle to curing hepatocellular carcinoma (HCC). Acid‐sensing ion channel 1a (ASIC1a) has critical roles in all stages of cancer progression, especially invasion and metastasis, and in resistance to therapy. Epithelial to mesenchymal transition (EMT) transforms epithelial cells into mesenchymal cells after being stimulated by extracellular factors and is closely related to tumour infiltration and resistance. We used Western blotting, immunofluorescence, qRT‐PCR, immunohistochemical staining, MTT, colony formation and scratch healing assay to determine ASIC1a levels and its relationship to cell proliferation, migration and invasion. ASIC1a is overexpressed in HCC tissues, and the amount increased in resistant HCC cells. EMT occurred more frequently in drug‐resistant cells than in parental cells. Inactivation of ASIC1a inhibited cell migration and invasion and increased the chemosensitivity of cells through EMT. Overexpression of ASIC1a upregulated EMT and increased the cells' proliferation, migration and invasion and induced drug resistance; knocking down ASIC1a with shRNA had the opposite effects. ASIC1a increased cell migration and invasion through EMT by regulating α and β‐catenin, vimentin and fibronectin expression via the AKT/GSK‐3β/Snail pathway driven by TGFβ/Smad signals. ASIC1a mediates drug resistance of HCC through EMT via the AKT/GSK‐3β/Snail pathway.